Detection of the Atherosclerotic PCSK9 gene Inhibitors Through in silico Method to Improve Targeted Therapy - Sabarinathan Sethuramalingam; Revathy Leena Ravi; Janet Rani Rajiah (Biology, Medicine, & Natural Product Chemistry, 2022)
The PCSK9 is one of the most important marks for the evolution of therapeutic agents for atherosclerosis because its interaction with low-density lipoprotein receptors causes atherosclerosis. Protein-ligand interactions help us to understand the true mechanism of pharmacological action. This study seeks to identify the most powerful suppression options for PCSK9. Initially, the reported ACE inhibitors were included in pharmacophore modeling using PharmaGist. Next, ZINCPHARMER was used to screen the selected model against a ZINC database to identify putative drug candidates docked to the target protein to understand the interactions. The 10 best pharmacological candidates for PCSK9 with a binding energy of 9.8-8.2 kcal mol-1 were identified by molecular docking and their pharmacokinetic properties and oral bioavailability were evaluated. The (S) severalplant obtained chemicals have been discovered, including anti-hypersensitive drugs such as â€œCanadine, Hesperetin, and Labetalolâ€. According to Biochemistry, these compounds formed a stable â€œprotein-ligandâ€ complex. The (S) canadine PCSK9 complex had the lowest RMSD and was the most stable. Future in vitro studies could identify (S) canadin as a promising atherosclerosis inhibitor for the evolution of novel PCSK9 inhibitors.